Measuring the concentration of uranium in the Qayyarah oilfield and refinery - Mustafa A. Mahmoud; Rasheed M. Yousuf (Tikrit Journal of Pure Science)
In this research, the Concentrations of uranium and radon gas were measured in the samples collected from the Qayyarah refinery and field, which is located south of Mosul. The samples included soil and water associated with the production of oil, sludge and crude oil. After prepared samples, the radioactivity was measured using the CR-39 solid-state nuclear trace detector. Radon levels ranged between 10.79-19.67  in soil samples, and in water samples 7.25  , in sludge samples 13.42-16.96  and in crude oil 8.57 . While uranium concentration levels, ranged in soil samples from 0.870 - 1.457 , in water samples 0.585  , in sludge samples 1.299 - 1.369 , and in crude oil samples 0.692 . These results indicate that it is within the internationally permissible limits, as the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) determined the value of uranium in soil at 32  and in water at 50 , and the International Atomic Energy Agency (IAEA) determined the value of uranium in The slag has a value of  and the International Association of Oil and Gas Producers (IOGP) has determined the value of uranium in crude oil    and therefore does not pose any danger to the lives of workers in the refinery. field and environment.